CT-Based Radiomics Showing Generalization to Predict Tumor Regression Grade for Advanced Gastric Cancer Treated With Neoadjuvant Chemotherapy - Chen, Yong; Xu, Wei; Li, Yan-Ling; Liu, Wentao; Sah, Birendra Kumar; Wang, Lan; Xu, Zhihan; Wels, Michael; Zheng, Yanan; Yan, Min; Zhang, Huan; Ma, Qianchen; et al. (Frontiers in Oncology, 2022)
Objective The aim of this study was to develop and validate a radiomics model to predict treatment response in patients with advanced gastric cancer (AGC) sensitive to neoadjuvant therapies and verify its generalization among different regimens, including neoadjuvant chemotherapy (NAC) and molecular target therapy. Materials and Methods A total of 373 patients with AGC receiving neoadjuvant therapies were enrolled from five cohorts. Four cohorts of patients received different regimens of NAC, including three retrospective cohorts (the training, internal and external validation cohorts) and a prospective Dragon III cohort (NCT03636893). Another prospective SOXA cohort received neoadjuvant molecular targeted therapy (ChiCTR-OPC-16010061). All patients underwent computed tomography before treatment and thereafter tumor regression grade (TRG) was assessed. The primary tumor was delineated and 2452 radiomics features were extracted for each patient. Mutual information and random forest were used to dimensionality reduction and modeling. The performance of the radiomics model to predict TRG under different neoadjuvant therapies was evaluated. Results There were 28 radiomics features selected. The radiomics model showed generalization to predict TRG for AGC patients across different NAC regimens, with AUCs (95% interval confidence) of 0.82 (0.76~0.90), 0.77 (0.63~0.91), 0.78 (0.66~0.89), 0.72 (0.66~0.89) in the four cohorts, with no statistical difference observed (all p > 0.05). However, the radiomics model showed poor predictive value on the SOXA cohort (AUC, 0.50 [0.27~0.73]), which was significantly worse than the training cohort (p = 0.010). Conclusion Radiomics is generalizable to predict TRG for AGC patients receiving NAC treatments, which is beneficial to transform appropriate treatment, especially for those insensitive to NAC.